Impact of climate change and social determinants on the spatial and epidemiological distribution of tuberculosis in the state of Pará: a perspective for COP 30 - G.A. Tavares-Cohén; A.P. Simões-Castro; C. Andrade-Sales; P.A Mendonça-Cavalcante; M.P. Moreira-Sena; B.C. Brito-Alves; U.G. El-Awar; A.W. Araújo-Sardinha; C.H.M. Azevedo-Ribeiro; J.L. Fernandes-Vieira; L.W. Pereira-Sena (Brazilian Journal of Biology)
Abstract Tuberculosis is a critical public health challenge in Brazil, with the state of Pará reporting high incidence rates driven by social inequalities, rapid urbanization, and adverse climatic conditions. This study analyzes the epidemiology of tuberculosis in the Metropolitan Region of Belém from 2018 to 2022, correlating social and environmental determinants with the impacts of climate change. Georeferenced data, temporal analysis, and predictive modeling were employed to identify epidemiological patterns and high-incidence clusters. Belém accounted for 60.1% of cases in the region, highlighting the influence of population density and socioeconomic vulnerabilities exacerbated by extreme climatic events. The findings underscore the need to integrate public policies and sustainability, emphasizing COP30 as an opportunity to catalyze both local and global actions.